Assessing students’ performance in software requirements engineering education using scoring rubrics - Mkpojiogu, Emmanuel O. C.; Hussain, Azham (2017)
The study investigates how helpful the use of scoring rubrics is, in the performance assessment of software requirements engineering students and whether its use can lead to students’ performance improvement in the development of software requirements artifacts and models.Scoring rubrics were used by two instructors to assess the cognitive performance of a student in the design and development of software requirements artifacts.The study results indicate that the use of scoring rubrics is very helpful in objectively assessing the performance of software requirements or software engineering students.Furthermore, the results revealed that the use of scoring rubrics can also produce a good achievement assessments direction showing whether a student is either improving or not in a repeated or iterative assessment.In a nutshell, its use leads to the performance improvement of students.The results provided some insights for further investigation and will be beneficial to researchers, requirements engineers, system designers, developers and project managers.